STEM Integrated Problem Based Learning: The Implementation and Roles in Science Learning - Simanjuntak, Yanni Irma Waty; Purwaningsih, Dyah (Jurnal Pendidikan MIPA, 2024)
This study aims to explore how the STEM integrated problem based learning model implemented and its role in science learning. Systematic literature review was the method used in this review. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) approach was adopted for this review. The search is based on the keyword “problem based learning”, “STEM”, “science learning”, “chemistry learning”, “physics learning”, and “biology learning”. All of 15 research articles reviewed in this paper were collected from well-known databases such as SCOPUS, ERIC, and Google Scholar. According to the review, STEM integrated PBL uses problem-based learning procedures to implement STEM education. STEM components (Science, Technology, Engineering, or Mathematics) are integrated in all five phases of problem-based learning. This review provides evidence that STEM integrated problem based learning can enhance students’ critical thinking, science process skills, science literacy, achievement, problem solving skills, learning interest, learning motivation, and conceptual understanding in science learning. Therefore, science learning problems related to these variables have the potential to be overcome using STEM integrated PBL.        Keywords: problem-based learning, science learning, stem. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp686-700